SMART GARDEN INTELLIGENT CONTROL SYSTEM IN COMMERCIAL HORTICULTURE AND ITS PRACTICAL IMPLEMENTATION - Andrey Anatolyevich ZAVRAZHNOV; Anatoly Ivanovich ZAVRAZHNOV; Igor Alexandrovich ELIZAROV; Victor Nikolaevich NAZAROV; Alexander Alexandrovich TRETYAK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This article discusses the Smart Garden concept in the frames of development of modern commercial horticulture. Composition and purposes of the automated complex elements are presented, intended for adjustment of soft- and hardware of intelligent control system of commercial garden. The structure of intelligent monitoring and control system for the automated complex is presented. Selection of LoRa wireless standard and network for data acquisition from territorially distributed monitoring and control sensors is substantiated. A variant of development of automated technologist workstation for Smart Garden automated complex is discussed. It has been established that an increase in the yield of fruit and berry plantations by 20% will provide a return on capital investments of about 200 thousand rubles per hectare within one year.